Web-based Vulnerability Analysis and Detection - Yadav, Narendra Singh; Rounak, Ritek; Sharma, Prakash Chandra (International Journal of Sensors Wireless Communications and Control, 2024)
Introduction: In today’s digital world, protecting organizations from breaches, hacking, data theft, and unauthorized access is key. Web-based vulnerability analysis and detection is a big part of that. Method: This research introduces a new approach to web-based vulnerability assessment by combining advanced automated tools with human expertise, a complete way to identify, rank, and fix critical vulnerabilities in web applications and websites. Our research presents a new automated scanner built with Python and Selenium which can detect a wide range of vulnerabilities including SQL injection, cross-site scripting (XSS), and emerging threats. The tool’s modular architecture and regular expression-based detection methods allow for flexibility and speed in detecting common and uncommon vulnerabilities. We propose a framework for vulnerability ranking so organizations can prioritize their fix efforts. Our approach considers exploiting potential, severity, and patch availability to give a more accurate risk assessment. Through real-world web application testing we demonstrate the effectiveness of our approach in detecting and fixing vulnerabilities. Result: Our results show significant improvement in detection accuracy and speed compared to traditional methods, especially for complex and dynamic web applications. This research adds to the body of knowledge in web security and vulnerability management by combining advanced automated scanning with human expertise. Conclusion: Our findings provide practical advice for organizations looking to improve their cybersecurity in the ever-changing digital world.
Keywords: Cross-site scripting